In an age of experts : the changing role of professionals in politics and public life - Brint, Steven G. (Book collections on Project MUSE., 1994)
Since the 1960s the number of highly educated professionals in America has grown dramatically. During this time scholars and journalists have described the group as exercising increasing influence over cultural values and public affairs. The rise of this putative "new class" has been greeted with idealistic hope or ideological suspicion on both the right and the left. In an Age of Experts challenges these characterizations, showing that claims about the distinctive politics and values of the professional stratum have been overstated, and that the political preferences of professionals are much more closely linked to those of business owners and executives than has been commonly assumed.